Perfil neurolinguístico comparativo das demências tipo Alzheimer e não Alzheimer - Soares, Cândida Dias (2010)
The national surveys of dementia and its implications for language, although in small numbers, line up with the international literature in the early trends of research. The articles presented were intended to draw a profile comparison between the differential Neurolinguistics degenerative dementia of Alzheimer type and non-Alzheimer's and dementia compare the two groups with a control group. The study was conducted from March 2008 to December 2009 were evaluated in 90 participants in the Dementia Clinic of the Hospital das Clinicas, Federal University of Goias The sample consisted of 30 patients with frontotemporal lobar degeneration (DLF), 30 patients with AD and 30 subjects with no dementia. We applied the following tests neurolinguistic: Boston Diagnostic Aphasia Examination (BDAE), Boston Naming Test (Boston Naming Test - BNT), Verbal Fluency Category for Semantics and Semantic and Phonemic Fluency (FAS), Token Test, subtest of Vocabulary / WAIS-R Similarities subtest of and / WAIS-R. To compare the performance of the group used the Mann-Whitney. All groups showed substantial linguistic differences. The APP group stood out from the other groups when compared to DA, showing that fluency, vocabulary, abstraction of ideas, understanding, reading and writing are more impaired. The FTD group reinforced the presence of dysfunction in semantic and phonemic verbal fluency DS group showed a statistically significant abstractive capacity with respect to the AD group. The DLF group is the group where the oral expression was shown to be noticeably compromised compared to the AD group. The language is therefore an indispensable tool to aid in the differential diagnosis of dementia.